2016
DOI: 10.1177/0081246316646296
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological profiles of adults and older adults with HIV

Abstract: The wider availability of highly active anti-retroviral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In a study by Carvalhal et al patients who were started on antiretroviral therapy had better neuropsychological pro les than those were not on medication 39 Patients with neurocognitive impairment had low scores on the on tests assessing working memory, visuospatial abilities, verbal learning and memory. Cassimjee et al showed that participants with HIV had poorer performance pro les in global cognitive functioning, memory, executive functioning, visuoconstructional ability, psychomotor functioning, and processing speed 40 which are cognitive domains tested by the afore-mentioned tools.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Carvalhal et al patients who were started on antiretroviral therapy had better neuropsychological pro les than those were not on medication 39 Patients with neurocognitive impairment had low scores on the on tests assessing working memory, visuospatial abilities, verbal learning and memory. Cassimjee et al showed that participants with HIV had poorer performance pro les in global cognitive functioning, memory, executive functioning, visuoconstructional ability, psychomotor functioning, and processing speed 40 which are cognitive domains tested by the afore-mentioned tools.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature examining performance on the Stroop in individuals living with HIV has shown mixed results. Some studies have shown similar performance on the Interference trial between HIV+ and HIVindividuals [2,15,16,17]. Others have found that individuals living with HIV perform signi cantly worse on the Interference trial than individuals who are HIV- [4,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals living with HIV commonly demonstrate a neuropsychological pro le with prominent disturbances in executive functioning [1,2,3,4,5]. In addition to the cognitive impairment associated with HIV, there is a high rate of substance use disorders in the HIV population, making it di cult to determine which cognitive disturbances are due to HIV or illicit substances.…”
Section: Introductionmentioning
confidence: 99%